Analisis kesalahan mahasiswa pada materi kekontinuan fungsi - Yukans, Septy Sari; Azka, Dea Alvionita; Darmawijoyo, Darmawijoyo; Susanti, Elsa (IKIP Siliwangi, 2024)
The Basic Calculus course is one of the compulsory courses that must be mastered by prospective mathematics teachers. This study aims to analyze the errors in the topic of Continuity in terms of prospective mathematics teachers’ ability to (1) interpret function graphs, (2) draw functions, and (3) utilize relevant concepts to construct written solutions. This is a descriptive study involving 27 second-semester of prospective mathematics teachers enrolled in Basic Calculus course as the subject of the study. Data were collected through written tests to all subjects, and interviews to selected subjects. The analysis of students' written answers revealed five types of errors: (1) errors in reading function graphs, (2) errors in sketching function graphs, (3) errors in determining the limit value of functions, (4) errors in understanding the concept of division by zero, and (5) errors in using the concept of Continuity. The findings of this study indicate that 66.67% of prospective mathematics teachers continue to demonstrate a limited proficiency in reading function graphs, 59.26% of students exhibit a lack of competence in function sketching, and 25.93% of students have a low level of ability in utilizing concepts to construct written solutions.